Testing dynamic consistency and consequentialism under ambiguity - Bleichrodt, Han; Eichberger, Jürgen; Grant, Simon; Kelsey, David; Li, Chen (European economic review, 2021)
Accounting for ambiguity aversion in dynamic decisions generally implies that either dynamic consistency or consequentialism must be given up. To gain insight into which of these principles better describes people’s preferences, we tested them using a variation of Ellsberg’s three-color urn experiment. Subjects were asked to make a choice both before and after they received a signal. We found that most ambiguity neutral subjects satisfied both dynamic consistency and consequentialism and behaved consistent with subjective expected utility with Bayesian updating. The majority of ambiguity averse subjects satisfied consequentialism, but violated dynamic consistency.
Gesehen am 14.07.2021